2007
DOI: 10.1021/ja0754002
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Structural Characterization of a Robust Octameric β-Peptide Bundle

Abstract: Proteins composed of α-amino acids are essential components of the machinery required for life. Stanley Miller's renowned electric discharge experiment provided evidence that an environment of methane, ammonia, water, and hydrogen was sufficient to produce α-amino acids. This reaction also generated other potential protein building blocks such as the β-amino acid β-glycine (also known as β-alanine); however, the potential of these species to form complex ordered structures that support functional roles has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 60 publications
10
83
0
Order By: Relevance
“…18,31 It has been shown that β and αβ-peptidic sequences are able to form quaternary structures with self-assembling helical building blocks. [32][33][34][35] These processes are very similar to the solvophobic interaction-driven tertiary/quaternary-structure formation observed for natural proteins. We planned to investigate the folding and the possibility of higher-ordered structure formation in alternating heterochiral trans-ACPC-containing β-peptide foldamer systems.…”
Section: Introduction and Aimssupporting
confidence: 64%
See 1 more Smart Citation
“…18,31 It has been shown that β and αβ-peptidic sequences are able to form quaternary structures with self-assembling helical building blocks. [32][33][34][35] These processes are very similar to the solvophobic interaction-driven tertiary/quaternary-structure formation observed for natural proteins. We planned to investigate the folding and the possibility of higher-ordered structure formation in alternating heterochiral trans-ACPC-containing β-peptide foldamer systems.…”
Section: Introduction and Aimssupporting
confidence: 64%
“…31 Various β-and α,β-peptide sequences have recently been found to form quaternary structures through self-assembling helical building blocks. [32][33][34][35] Infinite pleated sheet aggregates have also been observed, which appeared in the form of nanostrucuted fibrils. 113,129,210,213,214 Peptidic foldamers have the ability to fold into large-diameter helices, 68,215 which can participate in stable axial (head-to-tail) interactions through backbone hydrogen-bonds and side-chain interactions.…”
Section: Dosy-nmrmentioning
confidence: 94%
“…Extensive solution characterization is consistent with the formation of an octamer, and indicates that these helical bundles unfold with a protein-like thermal denaturation profile, and have kinetic and thermodynamic stabilities only slightly less than those of natural proteins [61••]. Substitution of multiple residues has generated a virtually identical structure with enhanced kinetic and thermodynamic stability [62]. This robustness has likely not been fully exploited.…”
Section: Peptoidsmentioning
confidence: 96%
“…It has been shown that peptidic foldamers are able to fold cooperatively into helix bundles; [20] β-and α,β-peptide sequences that were disordered at low concentrations have recently been shown to form quaternary structures through self-assembling helical building blocks. [21][22][23][24] Infinite pleated sheet aggregates were also observed, which eventually appeared in the form of nanostructured fibrils. [25][26][27][28][29] These processes are very similar to those leading to the formation of solvophobic interaction-driven tertiary/ quaternary structures observed for natural proteins.…”
Section: Introductionmentioning
confidence: 96%